THE EFFECT OF CINEMATIC LIGHTING ON STORY EMOTIONS IN 3D ANIMATION FILM - Sugiarto Sugiarto; Santi Widiastuti (STEKOM PRESS, 2020)
Main Objective: The objective of this research is to complete the exciting and fictive effects of each color and lighting type when practiced in 3D animation setting. In addition, this research also proposes several lighting design recommendations in 3D animation. Background problem: The main sense for the advance of animated films is cinematic lighting effects. Various techniques and approaches have been planned to create lighting effects, but how these effects affect the viewer’s sentimental sense and especially the storytelling practice is not understood. Novelty: The results of the emotional effects of lighting styles show that these effects are not shown in an imposing aspect, which means, not all lighting style affects the feelings on each scale. In this study, several differences were found in several color scales with different cinematic meanings. Research Method: The research method used is quantitative and subjective data analysis adopting a qualitative grounded theory coding with several animated video scenes developed with various colors and low and high-key statistical lighting designs to analyze and measure the effects of different lighting designs. Finding/Result: The finding of this study indicate that cinematic lighting influences the emotional impact of scenes and stories in plan. Conclusion: This study also confirms the current lighting approach, according to the result of this study, it brings guidance on how certain lighting and color techniques can be adopted to influence the audience in 3D animation about feelings and story perception Keywords: Cinematic Lighting, 3D animation, Emotional Storytelling